Δ‐MnO2 Nanofibers: A Promising Cathode Material for New Aluminum‐Ion Batteries. Issue 9 (7th May 2020) - Almodóvar, Paloma; Giraldo, David A.; Chancón, Joaquín; Álvarez‐Serrano, Inmaculada; López, María Luisa
Abstract: δ‐MnO2 nanofibers, synthesized by using a simple, low‐cost sol‐gel method, showed high electrochemical performance as a cathode for rechargeable Al‐ion batteries (AIBs). δ‐MnO2 presented an initial discharge capacity of 59 mA h g −1 and stabilized at 37 mA h g −1 at a current rate of 100 mA g −1 after 15 cycles and for more than 100 cycles with almost a 99 % coulombic efficiency. Different plateaus in charge/discharge curves, consistent with CV peaks, revealed the Al‐ion insertion/deinsertion and the electrochemical stability of the battery. Moreover, different rate CV measurements revealed the pseudocapacitive behavior of δ‐MnO2 in AIBs. The obtained charge/discharge capacities are ten times higher than previous studies performed with this material. Ex situ Raman and high‐resolution TEM measurements in different charge/discharge states revealed structural information of δ‐MnO2 upon Al‐ion intercalation/deintercalation. Abstract : Material witness : Recent interest in aluminum‐ion batteries (AIBs) has increased, owing to the high theoretical capacity, low cost, sustainability and low flammability. δ‐MnO2 is proposed as a high‐performance material in AIB cathodes.